A Relationship The Suitability of Prescriptions for BPJS with The National Formulary to Level Of Patient Satisfaction in Hospital - Whisnu Ajie; Khristina Natalia (Jurnal Kesehatan, 2022)
This study aims to determine the suitability of prescriptions for BPJS outpatient BPJS with the national formulary, determine the level of patient satisfaction with pharmaceutical services, and determine the relationship between prescription conformity with the national formulary on the level of patient satisfaction at Hospital West Bandung. This type of research is a quantitative descriptive analysis. Data on the suitability of prescription writing with the national formulary were obtained from observation sheets. Each item on the recipe sheet is checked for compliance with the national formulary. Meanwhile, patient satisfaction data was obtained from a satisfaction questionnaire sheet. There are eight assessment indicators that must be filled out by respondents. The number of samples in this study were 97 prescription sheets and 97 respondents. Data were analyzed using ETA test. The results showed that 86% of prescriptions were in accordance with the national formulary, the majority of patients were satisfied with pharmaceutical services, and there was no significant relationship between the suitability of prescription writing with the national formulary on patient satisfaction.